2022
DOI: 10.1007/s40279-022-01756-2
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Ketone Supplements in Athletic Contexts: Past, Present, and Future

Abstract: The ketone bodies acetoacetate (AcAc) and β-hydroxybutyrate (βHB) have pleiotropic effects in multiple organs including brain, heart, and skeletal muscle by serving as an alternative substrate for energy provision, and by modulating inflammation, oxidative stress, catabolic processes, and gene expression. Of particular relevance to athletes are the metabolic actions of ketone bodies to alter substrate utilisation through attenuating glucose utilisation in peripheral tissues, anti-lipolytic effects on adipose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 319 publications
(867 reference statements)
1
43
0
1
Order By: Relevance
“…[ 11 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) was trapped on a "cyanide trap" as previously reported (22), to facilitate the removal of ammonia, the presence of which would otherwise lead to hampering of the following hydrolysis step and formation of side products. ]β-hydroxybutyrate (Fig.…”
Section: Radiopharmaceutical Preparationmentioning
confidence: 94%
See 1 more Smart Citation
“…[ 11 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) was trapped on a "cyanide trap" as previously reported (22), to facilitate the removal of ammonia, the presence of which would otherwise lead to hampering of the following hydrolysis step and formation of side products. ]β-hydroxybutyrate (Fig.…”
Section: Radiopharmaceutical Preparationmentioning
confidence: 94%
“…It is therefore unknown whether cardiac ketone metabolism can be satisfactorily determined using simple 1-or 2-tissue compartmental modeling. Finally, although various ketone ester drinks are becoming increasingly popular both to enhance athletic performance (19) and to treat patients with e.g. heart failure (20), no PET studies using oral ingestion of PET tracers have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Sports supplements have grown in awareness and use exponentially over the last four decades [15,16,17]. Historically, supplements have had the earliest push to sports where strength and power have a critical role in performance, with the prime examples being football and basketball.…”
Section: How Sports Supplements Have Been Employed In Similar Situationsmentioning
confidence: 99%
“…Finally, the knowledge gained from emerging technological advances such as continuous glucose monitoring is likely to further fine tune carbohydrate dietary recommendations. The second paper in this supplement examines the immense interest in ingesting ketone supplements in athletic settings [ 2 ]. The recent commercial availability of ingestible exogenous ketone supplements in the form of ketone salts and ketone esters, and other ketogenic compounds, results in an acute transient increase in circulating acetoacetate and β-hydroxybutyrate levels, which has been termed “acute nutritional ketosis” or “intermittent exogenous ketosis”.…”
mentioning
confidence: 99%
“…While a few studies suggested that exogenous ketone supplements may improve endurance performance, recovery, and over-reaching, most studies have failed to observe benefits of acute nutritional ketosis on performance or recovery. It is also clear that these exogenous ketone supplements are not a viable fuel for athletes engaging in intense exercise [ 2 ].…”
mentioning
confidence: 99%